(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article examines the system of international assessment of Arabic language proficiency, important personal and social characteristics of the pedagogical competence of a future Arabic teacher in achieving professional success, strategies that a future teacher should follow when teaching Arabic to people who do not speak аrabic.